2000
DOI: 10.1055/s-2000-10002
|View full text |Cite
|
Sign up to set email alerts
|

Single Umbilical Artery Is Associated With an Increased Incidence of Structural and Chromosomal Anomalies and Growth Restriction

Abstract: The objective to characterize neonatal outcome associated with ultrasonographic identification of a single umbilical artery. Pregnancies diagnosed with single umbilical artery antenatally were identified. All prenatal/antenatal and pediatric records were reviewed for maternal demographics, associated anomalies, karyotypic analysis, pregnancy complications, and neonatal outcome. Twenty-seven pregnancies complicated by fetal single umbilical artery were identified. Of the 27 pregnancies, 5 (18.5%) underwent preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 10 publications
7
37
0
3
Order By: Relevance
“…The literature includes conflicting recommendations regarding management when SUA is recognized prenatally. 1,3,4,[11][12][13][14][15][16] There is general agreement that targeted ultrasound, if not already done, is indicated due to the high incidence of associated anomalies, 1,3,4,13,15,16 but many believe that if no other anomalies are detected on ultrasound, further testing is unnecessary.…”
Section: Resultsmentioning
confidence: 99%
“…The literature includes conflicting recommendations regarding management when SUA is recognized prenatally. 1,3,4,[11][12][13][14][15][16] There is general agreement that targeted ultrasound, if not already done, is indicated due to the high incidence of associated anomalies, 1,3,4,13,15,16 but many believe that if no other anomalies are detected on ultrasound, further testing is unnecessary.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven series are based on cases diagnosed prenatally and significant differences in birth weight were demonstrated in four out of six studies that included control groups. 6,7,11,[13][14][15]18,[20][21][22][23] On the other hand, all post-natal studies have shown that birth weight is significantly lower in ISUA pregnancies compared to control pregnancies. 5,9,10,12 This is possibly related to the fact that these are the studies with greater sample size.…”
Section: Introductionmentioning
confidence: 98%
“…In our patient twin-to-twin transfusion was not detected by ultrasonography and Doppler examinations. As a result, SUA via growth restriction was considered as the cause of the intrauterine loss [10]. Fetuses with sonographically diagnosed SUA were observed to have a high prevalence of structural anomalies and chromosomal abnormalities [10] but isolated SUA was not associated with aneuploidy [1,11].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, SUA via growth restriction was considered as the cause of the intrauterine loss [10]. Fetuses with sonographically diagnosed SUA were observed to have a high prevalence of structural anomalies and chromosomal abnormalities [10] but isolated SUA was not associated with aneuploidy [1,11]. If SUA occurs together with IUGR or other associated defects, because of the high risk of aneuploidy, parents should also be counselled for amniocentesis [12].…”
Section: Discussionmentioning
confidence: 99%